Preparation and properties of antibacterial and mite-resistant TCM/PNA blend fiber. Issue 1 (April 2019) - Huang, Xian; Yu, Husheng; Wang, Ze
Abstract: The acrylic fiber with antibacterial and mite-resistant function is prepared by wet spinning method by adding the extracts of LC with antibacterial function and the HX extract with the function of anti-mite to PAN (polyacrylonitrile) spinning liquid, and its morphological structure, basic properties of antibacterial and mite-resistant performance were tested. The results show that compared with pure PAN fiber, the fracture strength and elongation of the blend fiber of traditional Chinese medicine (TCM) / PAN decreased slightly with the addition of plant extract, and the thermal stability is improved. The inhibitory rate of the quantitative test is 93.83%; the removal rate of mites by TCM/PAN blend fiber non-woven fabrics is 83.21%, which had strong effect of preventing mites.